Case Report: Proximal Phalangeal Fracture Management in a European Bison (Bison bonasus) - Hoby, Stefan; Steiner, Adrian; Jucker, Simone; Bähler, Hansjürg; Alsaaod, Maher (Frontiers in Veterinary Science, 2022)
Fracture of the digits is a well-known orthopedic condition in adult cattle, and mainly the distal phalanx (P3) is involved. To our knowledge, the treatment of fractures of the middle (P2) and proximal (P1) phalanges with orthopedic claw blocks has not yet been described in cattle and other ruminants. This report describes the first case of the successful management of a P1 fracture in an adult European bison. A 5-year-old female European bison (Bison bonasus) presented with severe weight bearing lameness of the left hind limb and a marked soft tissue swelling accentuated over the plantar and lateral aspects of the proximal and middle phalanges, associated with multifocal light bluish discoloration of the skin (hematoma) and increased local temperature. The cow was examined and managed because of a severely comminuted fracture of the lateral P1 of the left hind limb. Application of an orthopedic block on the healthy medial partner claw allowed to reduce the load of the affected digit. Combined with the administration of non-steroidal anti-inflammatory drugs, it supported immobilization and recovery. Radiographic re-evaluations at weeks 6, 9, and 11 after the injury revealed progressive callus formation and fracture consolidation. From week 9 onwards, until the end of treatment, no lameness was observed. The healing process was good, and both clinical and radiographical improvement were evident after immobilizing the affected digit by applying an orthopedic claw block on the healthy partner claw and administering non-steroidal anti-inflammatory drugs.